2016
DOI: 10.1371/journal.pone.0160387
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from Tetraspanin CD9 Are Potent Inhibitors of Staphylococcus Aureus Adherence to Keratinocytes

Abstract: Staphylococcus aureus is one of the primary causative agents of skin and wound infections. As bacterial adherence is essential for infection, blocking this step can reduce invasion of host tissues by pathogens. An anti-adhesion therapy, based on a host membrane protein family, the tetraspanins, has been developed that can inhibit the adhesion of S. aureus to human cells. Synthetic peptides derived from a keratinocyte-expressed tetraspanin, CD9, were tested for anti-adhesive properties and at low nanomolar conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…Finally, anti-CD9 is also tested for its anti-adhesive properties to inhibit bacterial adhesion to keratinocytes and has been shown to be effective in a tissue-engineered model of human skin infected with Staphylococcus aureus suggesting that CD9 inhibitors may be a valuable addition to current treatments of skin infection and underscore the potential of targeting CD9 in bacterial infectious diseases ( 99 ).…”
Section: Targeting Cd9 As Potential New Therapeutic Strategy For Persmentioning
confidence: 99%
“…Finally, anti-CD9 is also tested for its anti-adhesive properties to inhibit bacterial adhesion to keratinocytes and has been shown to be effective in a tissue-engineered model of human skin infected with Staphylococcus aureus suggesting that CD9 inhibitors may be a valuable addition to current treatments of skin infection and underscore the potential of targeting CD9 in bacterial infectious diseases ( 99 ).…”
Section: Targeting Cd9 As Potential New Therapeutic Strategy For Persmentioning
confidence: 99%
“…Further differentiation of keratinocytes at air-liquid interface results in stratified layers, closely resembling the human skin. De-vitalized de-epidermalized dermis (DED), obtained by discarding both epidermis and adipose tissue from human skin, can also be used as a more physiological support to grow keratinocytes (Lamb and Ambler 2014; Ventress et al 2016). In addition, either primary or immortalized keratinocytes can be used to construct the epidermal layer, although the widely used HaCaT cell line does not reach the terminal differentiation stage (Boelsma et al 1999;Schoop et al 1999).…”
Section: Skin Equivalent Versus Skin Explantsmentioning
confidence: 99%
“…Due to the fact that Staphylococcus aureus is the major cause of bacterial skin and soft tissue infections in humans (McCaig et al 2006) and the widespread emergence of antibiotic-resistant strains, recent studies have tested strategies to block this pathogen at the initial site of the infection. A study performed in a human full-thickness skin equivalent, constructed by keratinocytes and fibroblasts seeded on top of a DED scaffold, showed that a tetraspanin-derived peptide can halve the number of S. aureus adherent to keratinocytes as compared to a scrambled control peptide, without impairing keratinocyte viability (Ventress et al 2016). Although it is still not clear if S. aureus infection is the cause or the consequence of atopic dermatitis (AD), the low expression of cutaneous antimicrobial peptides (AMPs) in AD patients is thought to contribute to their increased susceptibility to infections (Ong et al 2002).…”
Section: Use Of Human Skin Models In Anti-infective Researchmentioning
confidence: 99%
“…The findings presented here provide evidence to support the hypothesis that the clinical chlorhexidine phenotype (in vivo decolonization tolerance) of some MRSA clones may be due to adhesion and intracellular invasion of keratinocytes. However, further experiments will be required, with prolonged chlorhexidine exposure and antibiotic co-treatment in primary cell cultures and skin models 56,57 to examine the effects of keratinocyte antimicrobial peptides, 58 and to extend our findings by identifying the bacterial factors involved in protection against chlorhexidine and additionally investigate the consequences of intracellular survival on the host cells.…”
Section: Accepted Manuscriptmentioning
confidence: 99%